O patrocínio esportivo sob a perspectiva de gênero: empresas patrocinadoras de equipes de volibol - Leite, Sandra Maira Siqueira Naves (2019)
The sport has gone through many changes over the past decades and, either due to its enormous capacity for mobilization, or due to its global reach promoted by the advance of new technologies, it generates business opportunities with matches, championships and events. Currently, the sport is part of an industry that generates billions of dollars a year. In a highly competitive market, companies have comprehended that their image association with sports promotes brand awareness, leverages sales, generates new business opportunities, strengthens relationships and bolsters communication with consumers. Sponsorship is one of the sports promotion tools that has stood out the most in recent years and, in some periods, shows growth rates above the traditional advertising market, with impressive figures. In this context, it is important to emphasize that the sport, since its origin, has a strong rapport with the male territory, and statements in which sponsors state that they have more interest in male modalities are generally accepted. In terms of representation, the 2016 Olympic Games were an important milestone for the female athletes, who had the greatest participation of history - almost forty-five percent of the total number of athletes. Given this achievement, it was considered important to reflect on sport from a gender perspective and to know in depth what are the determinants that guide the evaluation of sports sponsorship, of sports properties by the managers of the sponsoring brands. This study focused on the master sponsoring companies of 2017-2018 volleyball teams, which is the second sport in national preference and it also presents high technical balance and international performance between women's and men's teams. The methodology used was qualitative, of an exploratory nature, with a semi-structured questionnaire. The results obtained evidenced a balanced interest of the companies in the sponsorship of the feminine and masculine teams. The determinants of relationship and brand image stood out in the masculine teams, whereas the focus of the consumer, brand image and visibility predominated in the feminine teams.